National Disparities in Surgical Approach to T1 Rectal Cancer and Impact on Outcomes. Issue 11 (November 2016) - Gabriel, Emmanuel; Thirunavukarasu, Pragatheeshwar; Al-Sukhni, Eisar; Attwood, Kristopher; Nurkin, Steven J.
This study investigated disparities between patients who had local excision versus radical resection for T1 rectal cancer. A retrospective analysis was performed using the National Cancer Data Base, 2004 to 2011. Inclusion criteria consisted of patients with T1, N0 rectal adenocarcinoma that were <3 cm, well or moderately differentiated without perineural invasion. Patients were stratified based on local excision and radical surgery. The primary outcome was overall survival (OS). Secondary outcomes included 30-day mortality, unplanned readmission rates, and postoperative length of stay. A total of 2235 patients were identified; 1335 (59.7%) underwent local excision and 900 (40.3%) had radical surgery. Overall, radical surgery was associated with an improved 5-year OS rate compared to local excision (0.86 vs 0.78, P = 0.009), increased unplanned readmission (6.5% vs 2.7%, P < 0.001), and longer postoperative length of stay (6.9 days vs 3.1 days, P < 0.001). For patients who had local excision, insurance status was an independent predictor of OS. Compared to patients with private insurance, those with government plans or no insurance had poorer OS (hazard ratio = 1.77 and 17.45, respectively, P = 0.006). Further study is warranted to understand the reasons accounting for this disparity in surgical approach to T1 rectal cancer.